Snack Tower as A Contemporary Business Opportunity to Increase Village Income - Ikhtiari, Kirana; Nurfadila, Nurfadila; Ibrahim, Fifi Nurafifah; Syam, Hasnidar; Shaleh, Musliha (Advances in Community Services Research, 2024)
Purpose: The specific aim was to provide training in making Snack towers, gift items made from snacks shaped like tarts or birthday cakes. These towers serve as an alternative option for gifts during important occasions. Study design/methodology/approach: The community service activity involved conducting training sessions in Snack tower making for the residents of Julukanaya Village to equip the participants with the necessary skills and knowledge to create Snack towers. The production process was designed to be cost-effective, allowing for adjustments based on individual budget constraints. The affordability of Snack towers led to high demand among the public. Findings: The community service activity successfully trained the residents of Julukanaya Village, enabling them to acquire new skills. The interest and enthusiasm of the community members were encouraged through this program, with the potential to increase their economic income. The Snack Tower production was identified as a contemporary business opportunity, presenting a viable option for new entrepreneurs. The Snack Tower business can also create employment opportunities for the surrounding community. Originality/value: The affordability and popularity of Snack towers make them a valuable option for gifts and presents during important occasions. The collaboration between the community and the trainers in this program can unleash the entrepreneurial potential of the Julukanaya Village community and contribute to the region's economic growth.